Administrative and Ethical Issues in Ghana’s Public Administration - Fobih, Nick (Advances in Social Sciences Research Journal, 2021)
This study examines some of the major administrative and ethical challenges facing Ghana’s public administration, with regard to the issues associated with the country’s governance processes and public sector service delivery. The methodology used is based on the qualitative approach with combined sources from primary and secondary data and the case study method. The findings in the study show that whereas Ghana’s democracy has made significant inroads over the years since the 1992 democratic transition, a number of administrative and ethical issues hinder the country’s public administration processes and procedures, which require immediate government attention to address them more appropriately. The study recommends that the government (executive branch) and the bureaucracy (Ministries, Departments and Agencies) should make frantic efforts towards promoting effective and efficient service delivery system and government accountability for accelerated national development. The study’s implication for theory is that it will inform its readers about the different perspectives on the topic discussed. Given the service delivery and corruption challenges in Ghana’s public sector, the recommendations will go a long way to help address some of the problems facing Ghana’s MDAs and the government in general. The significance of the study is that it provides key insights into important issues in Ghana’s public administration, which can serve as useful lessons for the government, public institutions and the bureaucracy. The outlined challenges and recommendations will inform the government, MDAs and other government agencies of the need to improve governance and administration in order to accelerate the country’s political and socio-economic development. This study further contributes towards academic discussions on the administrative and ethical issues hampering the effective delivery of services and public and administration in Ghana and Africa in general.